Variability of eight Algerian oleaster ecotypes (Olea europaea subsp. europaea var. sylvestris [Mill.] Lehr): pollen and exine morphology in relation to geo-climatic effect. Issue 4 (4th July 2021) - Khouatmiani, Khedidja; Belhadj, Safia; Tonetto, Alain; Assie, Axel; Mevy, Jean Philippe; Gauquelin, Thierry
Abstract: Pollen characters of the Algerian oleaster ( Olea europaea subsp. europaea var. sylvestris [Mill.] Lehr) from eight ecotypes were analysed to evaluate the geo-climatic effect of their environment. Samples were collected along an altitudinal gradient from western to central Algeria. Eighteen morphological characters of the pollen grains were studied using scanning electron microscopy (SEM). The results show significant inter-populations variability. The geo-climatic conditions, duration and timing of dry periods vary from one area to another. Depending on the area, the length of the dry period ( P p  ≤ 2 T ) coincides more or less with anthesis periods. No significant geo-climatic effects on exine parameters were detected, except for lumina density (LD) and mean lumina diameter (Lm). However, polar axis ( P ), pollen size index (PSI) and pollen colpis length (PCL) were found to be related to latitude, longitude and temperature. LD and Lm were strongly linked to the pollen parameters, resulting in variation in pollen shape and size. Depending on the geo-climatic conditions, three morphotypes appear. The morphotype from a site with high temperature, low humidity associated with a long dry period is characterised by small pollen size, low lumina surface area and high lumina density/100 μm 2 and vice versa. The results indicate that the exine has played an important role in the environmental adaption in these wild populations.